1997
DOI: 10.1523/jneurosci.17-12-04809.1997
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Visual Motion Information and Reliability in Spiking and Graded Potential Neurons

Abstract: We investigated the information about stimulus velocity inherent in the membrane signals of two types of directionally selective, motion-sensitive interneurons in the fly visual system. One of the cells, the H1-cell, is a spiking neuron, whereas the other, the HS-cell, encodes sensory information mainly by a graded shift of its membrane potential. Using a pseudo-random velocity waveform by which a visual grating is moving along the horizontal axis of the eye, both cell types follow the stimulus velocity at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 39 publications
9
65
0
Order By: Relevance
“…Because computations that underlie direction selectivity inevitably require time constants of some tens of milliseconds [50], they attenuate the neural responses to high-frequency velocity fluctuations (Fig. 3c) [51,52]. Hence, TC depolarizations are sufficiently pronounced to elicit spikes with a millisecond precision only when the velocity changes are very rapid and large [17,18,53].…”
Section: Accuracy Of Encoding Of Optic Flow Informationmentioning
confidence: 99%
“…Because computations that underlie direction selectivity inevitably require time constants of some tens of milliseconds [50], they attenuate the neural responses to high-frequency velocity fluctuations (Fig. 3c) [51,52]. Hence, TC depolarizations are sufficiently pronounced to elicit spikes with a millisecond precision only when the velocity changes are very rapid and large [17,18,53].…”
Section: Accuracy Of Encoding Of Optic Flow Informationmentioning
confidence: 99%
“…5e, f). The response of the neuron thus reflects the animal's rotational velocity in a highly non-linear fashion (Egelhaaf and Reichardt 1987;Haag and Borst 1997;Kern et al 2001b;van Hateren et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been found that the velocity of a randomly fluctuating motion stimulus is represented by spiking and graded potential TCs similarly well -as long as the pattern moves in the cell's preferred direction. Velocity fluctuations above 10-20 Hz are encoded only poorly by TCs of either signalling mode [35]. This feature is only partly attributable to neuronal noise.…”
Section: The Performance Of Spiking and Graded Potential Neurons In Ementioning
confidence: 89%
“…This feature is only partly attributable to neuronal noise. It is also the consequence of the fact that the stimulus-induced responses of TCs do not only depend on pattern velocity but also on its higher temporal derivatives [35,36]. In a recent study of a TC that generates both graded potential changes and spike-like events, it was concluded that more information about stimulus velocity is encoded by the graded response than by the spike-like events [37 • ].…”
Section: The Performance Of Spiking and Graded Potential Neurons In Ementioning
confidence: 99%
See 1 more Smart Citation